2013
DOI: 10.1159/000347090
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Anterior Cingulate Cortex Neurochemistry in Adolescents with Generalized Anxiety Disorder

Abstract: Background/Aims: This study used proton magnetic resonance spectroscopy (1H MRS) to evaluate the neurochemistry of the anterior cingulate cortex (ACC) in adolescents with generalized anxiety disorder (GAD). Methods: Adolescents with GAD (n = 10) and healthy subjects (n = 10) underwent a 1H MRS scan at 4 T. Glutamate (Glu), N-acetyl aspartate, creatine (Cr) and myo-inositol concentrations were measured in the ACC and were compared between untreated adolescents with GAD and age- and sex-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 91 publications
1
29
1
Order By: Relevance
“…Moreover, an inverse correlation was observed between hippocampal NAA and body mass index as well as higher worry predicted low hippocampal NAA and PCr + Cr. Lastly, Strawn et al (2013) recently reported no significant alterations in glutamate/PCr + Cr ratios in the anterior cingulate of adolescents with GAD; however, a positive correlations between glutamate/PCr + Cr and anxiety symptoms severity.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, an inverse correlation was observed between hippocampal NAA and body mass index as well as higher worry predicted low hippocampal NAA and PCr + Cr. Lastly, Strawn et al (2013) recently reported no significant alterations in glutamate/PCr + Cr ratios in the anterior cingulate of adolescents with GAD; however, a positive correlations between glutamate/PCr + Cr and anxiety symptoms severity.…”
mentioning
confidence: 90%
“…Briefly, among the 11 studies retrieved, the majority employed a multi-voxel (N = 7) instead of a single-voxel (N = 4) ¹H MRS technique and a 1.5 T scanner (N = 6) instead of a 3 T (N = 4) or a 4 T (N = 1) scanner. Interestingly, all the ¹H MRS studies on GAD, except for two studies Abdallah et al 2012a;Strawn et al 2013), focused on brain regions within the hippocampus and dorsolateral prefrontal cortex (DLPFC).…”
mentioning
confidence: 99%
“…Therefore, it is assumed that both brain functional deficits and cellular metabolic alterations might be associated with GAD symptoms. However, the nature of the causality between functional and metabolic brain alterations is unclear, since brain functional or neurochemical studies (Blair et al, 2008;Mathew et al, 2008;Monk et al, 2008;McClure et al, 2011;Price et al, 2011;Ball et al, 2013;Strawn et al, 2013) have been separately performed. A combined fMRI and 1 H-MRS study would be valuable to investigate whether the brain functional abnormality is associated with the metabolic changes in connection with emotional dysregulation and cognitive deficit in patients with GAD.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that glutamate is increased in the ACC in patients with general anxiety disorder (Strawn et al, 2013) or social anxiety disorder (Pollack, Jensen, Simon, Kaufman, & Renshaw, 2008). Excess glutamate in anxiety is not only found in categorical comparisons, but also correlates with anxiety severity.…”
Section: Proton Magnetic Resonance Spectroscopy Is a Noninvasive Neuro-mentioning
confidence: 99%